FARM FROM HOME, OPTIMALISASI PEKARANGAN DENGAN BUDIDAYA TANAMAN “EMPON-EMPON”, SEBAGAI UPAYA MENJAGA DAYA TAHAN TUBUH (IMUNITAS), DI TENGAH DAN PASCA PANDEMI COVID 19 - Ari Handriatni (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2020)
The Covid 19 pandemic, where the event was the spread of the 2019 corona virus disease, so it is called the corona virus disease 2019, abbreviated as Covid 2019 throughout the world. Each person has a different response to Covid 2019, most people exposed to the virus will experience mild to moderate symptoms, and will recover without the need to be hospitalized. The transmission of covid 2019, through air and droplets, so it is necessary to maintain growth resistance or immunity by consuming herbal drinks, which come from empon-empon plants or plant-finding plants. To get these materials, you can do farming in your own home with your family. The government has launched work from home since the Covid 19 pandemic, before the new normal was enforced. To overcome boredom at home for months, Farm From Home is the right choice so that farming with family is very enjoyable. The empon-empon plant contains a lot of curcumin compounds, essential oils which are antioxidants, useful antioxidants for the body to protect cells from free radical damage, can increase stamina when consumed as herbal drinks.